Schizophrenia Treatment - The New Facets - Yu-Chih Shen (IntechOpen, 2016)
Schizophrenia treatment has many facets. This book begins with the glutamatergic and GABAergic hypofunctioning contribute to the schizophrenic symptoms and their current targeted therapeutics. The genetic, epigenetic, and immune etiologies of schizophrenia and their potential targeted therapeutics as approached in this book are interesting. Understanding cognitive biases and delusional circuits in schizophrenia is important; several behavioral cognitive therapies working on the reduction and avoidance of these cognitive biases are demonstrating their effectiveness. Advances in schizophrenia treatment followed, including transcranial magnetic stimulation and special sport program, are presented at the book's end.
English
Keywords: Medicine; Neurology; Mental and Behavioural Disorders and Diseases of the Nervous System; Health Sciences